Revitalisasi Peran Kader Kesehatan dalam Program Pencegahan dan Penanggulangan Stunting - Dian Isti Angraini; Efriyan Imantika; Merry Indah Sari; Ety Apriliana; Fitria Saftarina (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
The purpose of this programme is to revitalize the role of health cadres in stunting prevention and control programs. The methods used in this programme are focus group discussions as the basis for making training modules, training health cadres with interactive lectures and discussion techniques, as well as simulating how to educate and assess toddler growth using maternal and child health books (KIA). This programme was carried out for 2 days and took place at the Tanjung Sari Natar Health Center, South Lampung Regency. The participants were 30 people who were health cadres in the Tanjung Sari Natar Health Center work area, South Lampung Regency. The results of the evaluation of the implementation of the programme found that there was an increase in participants' understanding of 93.33% to a good understanding, 6.67% of participants had a fairly good understanding, and none of the participants had a poor understanding of balanced nutrition in the first 1000 days of life (nutrition of pregnant women, breastfeeding mothers, infants and toddlers), stunting prevention, assessing the growth and development of toddlers and educational-information-communication techniques. The average pretest result was 59.5 and an increase in the posttest result was 85.5. Based on the analysis using the Wilcoxon test, it was found that there was a statistically significant mean difference between the pretest and posttest values of the participants regarding of balanced nutrition in the first 1000 days of life (nutrition of pregnant women, breastfeeding mothers, infants and toddlers), stunting prevention, and assessing the growth (p=0.000).